(3GdahGJM GdEdgjI hGdeaGJjM GdZjHjIs - (3eMeO Hf ESMGb Hf eMeO Hf jhSa Hf Ydj Gdbhfhj GdQhej, UOQ GdOjf,J (B673 (3g` s
(3ChdgG (B:s
(3SHMGfc dG Yde dfG EdG eG YdeJfG s
(3BNQgG (B:s
(3hef LedI ef CWGY Gddg hQShdg Je Pdc s
(3Vef eLehY , JQJjHgG (B: (3GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B30s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeQcRjI GdUhajI (B- (3GdehUd (B(1061 (3S(B) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs